ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN (Studi Pada Perusahaan Yang Terdaftar Dalam Indeks LQ45) - Soruh, Nelciana Yulita; JMV, Mulyadi; Suyanto (SEKOLAH PASCASARJANA PRESS, 2018)
Company value is an investor's perception of the company that is associated with stock prices. Company value can be influenced by internal factors and external factors. Internal factors can be measured using financial ratios based on the company's financial statements. The financial ratio in this study is illustrated by the value of Debt to Equity Ratio (DER), Current Ratio (CR), Company Size (Ln) and Net Profit Margin (NPM). The external factors of the company can be in the form of inflation conditions that can affect the value of the company. This study aims to determine and analyze the effect of capital structure, liquidity, firm size, profitability and inflation on firm value both simultaneously and partially. The population in this study is for companies listed on LQ45 on the Indonesia Stock Exchange for the period 2012 - 2017. The samples in this study were selected using a purposive sampling method to obtain as many as 15 companies from 45 companies that will be used as research objects. The data analysis method used is a multiple linear regression analysis method with a significance level of 5%. The results of the research obtained are simultaneously capital structure, liquidity, company size, profitability and inflation affect the value of the company. While partially the size of the company that affects the value of the company. But the capital structure, liquidity, profitability and inflation do not affect the value of the company